Short-term comprehensive cardiac rehabilitation after AMI is associated with reduced 1-year mortality: results from the OMEGA study. (September 2014) - Rauch, Bernhard; Riemer, Thomas; Schwaab, Bernhard; Schneider, Steffen; Diller, Frank; Gohlke, Helmut; Schiele, Rudolf; Katus, Hugo; Gitt, Anselm; Senges, Jochen; ,
Background: The prognostic effect of early, comprehensive short-term cardiac rehabilitation on top of current, guideline-adjusted treatment of acute myocardial infarction has not sufficiently been evaluated. Design: Prospective cohort study. Methods: Within the OMEGA study population, the clinical course of 3560 patients still alive 3 months after acute myocardial infarction were evaluated by comparing patients who had attended to cardiac rehabilitation (70.6%) with those who did not. Total mortality and major adverse cerebrovascular and cardiovascular events, as well as non-fatal events, were evaluated within the time period of 4–12 months after hospital admission for acute myocardial infarction. The effect of cardiac rehabilitation on clinical events was estimated by using the propensity score method to adjust for confounding parameters in multivariate analysis. Results: Patients participating in cardiac rehabilitation were younger, more often had acute revascularization, less often experienced non-ST-elevation myocardial infarction, and less often had a history of diabetes or cardiovascular events. Total mortality (OR 0.46, 95% CI 0.27–0.77) and major adverse cerebrovascular and cardiovascular events (OR 0.53, 95% CI 0.38–0.75) were significantly lower in the rehabilitation group. Subgroup analysis including major clinical characteristics also revealed significantly reduced rates of total death and major adverse cerebrovascular and cardiovascular events in the rehabilitation group. Conclusions: Attendance to early, comprehensive short-term cardiac rehabilitation programmes on top of current guideline-adjusted treatment of acute myocardial infarction is associated with a significantly improved 1-year prognosis.